Negative news exposure does not affect risk or ambiguity aversion - Garcia Campos, Luis S.; Lempert, Karolina M. (Frontiers in Psychology, 2025)
IntroductionUncertain decisions can be risky (with known probabilities) or ambiguous (with unknown probabilities). Previous studies have found that negative affect can increase risk aversion and ambiguity aversion, but it is unknown if these effects generalize to more realistic negative stimuli. In real life, negative affect is frequently induced by exposure to news reports. Here, in two pre-registered studies, we examined how watching a negative news video influenced risk and ambiguity aversion.MethodsStudy 1 was conducted online in a sample of university students (n = 84), whereas Study 2 was done by a sample on Prolific (n = 229). Participants were randomly assigned to one of two groups. The negative news group viewed a news video about a car crash, while the control group watched a news video about train schedules. Then, all participants did a task in which, on each trial, they chose between a certain $5 reward or a gamble option. Half the gambles were risky (e.g., 50% chance of $10; 50% chance of $0), and half were ambiguous, so that the probabilities of the outcomes were not fully known.ResultsAlthough participants who watched negative news reported a significant increase in negative affect, they did not differ from the neutral news group in their risk or ambiguity preferences.DiscussionThese findings, when considered alongside other similar null findings in the literature, suggest that incidental negative affect might have no effect on decisions under uncertainty, unless the affect is misattributed to the choice itself.